Composite hydrogel coaxial stent
By using composite hydrogel coaxial scaffolds in alveolar bone repair materials, combining osteogenesis-induced components, antimicrobial peptides and exosomes, the shortcomings of existing materials in bone regeneration and antibacterialization are solved, and efficient teeth are achieved Groovary regeneration and antibacterial effects.
Patent Information
- Application Number
- CN202411556540.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the repair materials for alveolar bones after tooth extraction have limited sources, lack of sufficient antibacterial properties or poor osteoinductivity, which affects the efficiency and success rate of bone regeneration.
A composite hydrogel coaxial scaffold was developed to achieve bone regeneration and antibacterial effects by incorporating osteogenesis-induced components and antibacterial peptides into the carrier scaffold and loading exosomes in the inner core of the scaffold.
While maintaining good mechanical strength, the composite hydrogel coaxial bracket has excellent shaping ability, can flexibly fill the tooth extraction socket, promote bone regeneration and angiogenesis, and has significant antibacterial properties.
Smart Images

Figure CN119455121A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of medical materials and relates to a composite hydrogel coaxial stent, and more specifically, to a deformable composite hydrogel coaxial stent for alveolar bone regeneration after tooth extraction. Background Art
[0002] The use of biological materials at the same time as tooth extraction can minimize the absorption of alveolar bone, guide bone regeneration, promote the healing of defect areas, and provide guarantee for future repair treatment. At present, the biological transplant materials used in clinical practice mainly include autologous bone, allogeneic bone, xenogeneic bone, artificial synthetic materials, etc.
[0003] 1. Autologous bone transplantation refers to the transplantation of bone tissue from one location in the same body to another. Autologous bone has the advantages of biosafety and compatibility, is not prone to allergic reactions and immune rejection reactions, and has strong bone induction ability, so it is considered the "gold standard" for alveolar bone transplantation. Reference 1 observed the effect of autologous bone transplantation combined with platelet-rich fibrin in repairing severe alveolar bone defects. The results showed that in guided tissue regeneration surgery, the use of autologous platelet-rich fibrin combined with autologous bone filling can improve the periodontal microecological environment of patients with severe alveolar bone defects, reduce gingival tissue inflammation, promote alveolar bone tissue regeneration and repair, and reduce tooth mobility.
[0004] However, autologous bone transplantation faces many limitations: the first is its limited supply source, which is not suitable for large-scale bone reconstruction; in addition, the surgery requires the opening of an additional donor site, which undoubtedly increases the patient's trauma burden, and is often accompanied by significant swelling and pain after surgery. Excessive collection of autologous bone may also lead to a sharp decrease in the strength of the residual bone, and even induce pathological fractures in the donor site. These disadvantages significantly limit the wide range of its clinical applications. In recent years, although autologous tooth particles have shown potential as an emerging biomaterial for the preservation of alveolar bone sites, their support structure is insufficient when dealing with large-area bone defects, and the effect of maintaining spatial stability is poor. In addition, the preparation conditions are still controversial, so in-depth exploration is needed to optimize their application.
[0005] 2. Allogeneic bone mostly comes from donors, so there is no need to open a second surgical area, and its osteogenic activity and spatial stability are not much different from those of autologous grafts. Reference 2 found that when allogeneic decalcified freeze-dried bone combined with non-absorbable dense polytetrafluoroethylene membrane was used for site preservation, compared with the natural healing group, the site preservation group could significantly reduce the absorption of alveolar ridge height and width, and the effect was more significant in maintaining alveolar ridge width and buccal bone height.
[0006] Although allogeneic bone does not require an additional surgical area, its osteogenic activity and spatial stability are comparable to those of autologous bone transplantation, providing convenience for treatment. However, this method is also accompanied by potential risks such as rejection and cross infection, which are still the focus of discussion and concern in the medical community.
[0007] 3. Xenogeneic bone transplantation was initially used to treat periodontal bone defects, and has since been widely used in various types of bone defects in clinical practice. Bio-Oss bone transplant material is currently the most widely used and most studied xenogeneic bone transplant material in clinical practice. It has a porous structure and hydroxyapatite content similar to human bone tissue, including Bio-Oss bone powder and Bio-Oss collagen. Bio-Oss bone powder is a bovine bone matrix with organic matter removed, in granular form. Bio-Oss collagen consists of 10% collagen and 90% Bio-Oss bone powder. Reference 3 added microRNA-21 as a bioactive agent to Bio-Oss, and the results showed that the microRNA-mediated biofunctionalized scaffold significantly shortened the recovery time of the alveolar bone from the normal 2-3 months to 2 weeks, while improving the quality of the new bone in the alveolar socket. Reference 4 This retrospective study aims to analyze the clinical efficacy of two regenerative surgical methods (Bio-Oss particles combined with barrier membrane and Bio-Oss collagen alone) and help clinicians achieve better periodontal regeneration results under specific periodontal conditions. Reference 5 The results of the study showed that the method of using Bio-Oss Collagen to preserve extraction sites is feasible, with less damage and shorter operation time, and can achieve results similar to traditional extraction site preservation.
[0008] However, the disadvantage of xenogeneic bone is its strong immunogenicity, and the key to handling xenogeneic bone is to remove its immunogenicity. Bio-Oss bone powder, with its porous structure and slow degradation characteristics, performs well as a bone-guiding scaffold, promoting the growth of blood vessels and early osteoblasts. However, it lacks osteoinductivity and is difficult to shape. Clinically, Bio-Oss bone powder is often used in combination with barrier membranes, but there is a risk of membrane exposure infection, so antibacterial properties are also particularly important when biomaterials are applied in the oral cavity. In the subsequently developed Bio-Oss Collagen, 10% of collagen is used as a binder to aggregate and shape the dispersed Bio-Oss particles. After implantation in the body, the collagen part is gradually replaced by new bone tissue in about 4 to 6 weeks. However, considering the quality of new bone for alveolar bone regeneration and the shortened healing time of the alveolar socket, bone collagen still lacks the necessary bioactive components.
[0009] 4. According to their composition, synthetic materials can be divided into three categories: organic materials, inorganic materials and composite materials. As completely artificial products, these materials do not need to rely on donors, so they can be supplied in unlimited quantities and fundamentally eliminate the risk of disease transmission. In terms of inorganic materials, although they show good tissue compatibility and certain biological activity, it cannot be ignored that they are relatively brittle and relatively lacking in toughness. On the other hand, although pure collagen polymer materials have excellent toughness, they are difficult to meet strict mechanical performance standards. Given that hydroxyapatite is highly similar to the inorganic components of natural bone, and collagen is the main organic component in human bones, accounting for about 90% of organic matter, the composite of hydroxyapatite and collagen has become one of the current research hotspots in the field of biomedical engineering. Reference 6 focuses on loading the natural glycoside naringin with excellent biological and pharmacological properties into nHA / COL (nano-hydroxyapatite or collagen) scaffolds to prepare NG / nHA / COL (Naringin or nano-hydroxyapatite or collagen) scaffolds to promote the healing process of bone defects and characterize them using various analytical methods as well as cell and animal studies. Reference 7 deeply explores the physicochemical properties, biocompatibility and role of nano HA (hydroxyapatite) / collagen composites as scaffold materials in promoting bone regeneration.
[0010] Current artificial synthetic materials have many deficiencies in design and performance, such as coarse particles, excessive crystallinity or uneven two-phase composition. These problems directly affect the mechanical properties and biological activity of the materials, making it difficult to meet the ideal requirements of clinical applications.
[0011] Citations
[0012] Reference 1: Repair of severe alveolar bone defects with autologous bone and platelet-rich fibrin[J]. Chinese Journal of Tissue Engineering Research, 2025, 29(10): 2044-2051.
[0013] Reference 2: Evaluation of Healing at Molar Extraction Sites With andWithout Ridge Preservation: ARandomized Controlled Clinical Trial. JPeriodontol, 2017, 88: 241-249.
[0014] Cited document 3: Early healing of alveolar bone promoted by microRNA-21-loaded nanoparticles combined with Bio-Oss particles. Chemical engineering journal, 2020, 401(1).
[0015] Cited document 4: Clinical and radiographic evaluation of Bio-Oss granules and Bio-Oss Collagen in the treatment of periodontal intrabony defects:aretrospective cohort study. J Appl Oral Sci, 2024, 32: e20230268.
[0016] Reference 5: Clinical analysis of the preservation of extraction sites after maxillary molar extraction using Bio-Oss Collagen. Chinese Journal of Oral Implantology, 2023, 28(02): 90-96.
[0017] Cited document 6: Naringin Release from a Nano-Hydroxyapatite / CollagenScaffold Promotes Osteogenesis and Bone Tissue Reconstruction. Polymers (Basel), 2022, 14, 3260.
[0018] Reference 7: Nano-hydroxyapatite / collagen composite as scaffold material for bone regeneration. Biomed Mater, 2023, 18. Summary of the invention
[0019] Problem that the invention aims to solve
[0020] In the prior art, the restoration of alveolar bone after tooth extraction often relies on traditional bone transplant materials or biological scaffolds, but these materials have problems such as limited sources, lack of sufficient antibacterial properties or poor bone inductivity, which affect the efficiency and success rate of bone regeneration. Therefore, it is particularly important to develop a biological scaffold material that can flexibly fill the alveolar socket after tooth extraction and has excellent antibacterial properties to achieve site preservation.
[0021] In view of this, an object of the present invention is to provide a composite hydrogel coaxial stent.
[0022] Solutions for solving problems
[0023] [1] A composite hydrogel coaxial stent, comprising:
[0024] A carrier scaffold, the carrier scaffold comprising a scaffold body having a cavity formed by a gel mixture, wherein the gel mixture comprises a first hydrogel component and an osteogenic induction component; and
[0025] The inner core is filled in the cavity of the carrier support, and the inner core comprises a second hydrogel component.
[0026] [2] The composite hydrogel coaxial scaffold according to [1], wherein in the carrier scaffold, the mass ratio of the first hydrogel component to the osteoinductive component is 1:(5-15).
[0027] [3] The composite hydrogel coaxial stent according to [1] or [2], wherein the carrier stent is loaded with antimicrobial peptides;
[0028] Preferably, the antimicrobial peptide comprises a cationic antimicrobial peptide;
[0029] More preferably, the antimicrobial peptide comprises the amino acid sequence shown in SEQ ID NO: 1, or an amino acid sequence having one, two, three, four or five conservative substitutions compared with the amino acid sequence shown in SEQ ID NO: 1.
[0030] [4] The composite hydrogel coaxial stent according to any one of [1] to [3], wherein more than 1 μg of the antimicrobial peptide, preferably more than 2 μg of the antimicrobial peptide, is loaded per 1 mg of the carrier stent.
[0031] [5] The composite hydrogel coaxial stent according to any one of [1] to [4], wherein the second hydrogel component is loaded with exosomes.
[0032] [6] The composite hydrogel coaxial scaffold according to [5], wherein the exosomes are derived from mesenchymal stem cells;
[0033] Preferably, the exosomes are derived from bone marrow mesenchymal stem cells.
[0034] [7] The composite hydrogel coaxial stent according to any one of [1] to [6], wherein the first hydrogel component and the second hydrogel component each independently comprise one or a combination of two or more of porcine small intestinal submucosal gel, alginate, hyaluronic acid or collagen;
[0035] Preferably, the first hydrogel component and the second hydrogel component each independently comprise porcine small intestinal submucosal gel;
[0036] and / or,
[0037] The osteoinductive component includes one or a combination of two or more of hydroxyapatite, tricalcium phosphate, tetracalcium phosphate, octacalcium phosphate, calcium oxide, calcium silicate, calcium sulfate or calcium carbonate;
[0038] Preferably, the osteoinductive component comprises hydroxyapatite.
[0039] [8] A method for preparing the composite hydrogel coaxial stent according to any one of [1] to [7], comprising the following steps:
[0040] a step of preparing a carrier scaffold, wherein the osteogenic induction component is mixed with the first hydrogel component, added to a mold, and dried to obtain a carrier scaffold having a cavity; and
[0041] The step of filling the inner core is to fill the second hydrogel component into the cavity of the carrier stent to form a composite hydrogel coaxial stent.
[0042] [9] The preparation method according to [8], wherein in the step of filling the inner core, the second hydrogel component is loaded with exosomes;
[0043] Optionally, before the step of filling the inner core, a step of gel-loading exosomes is included, which includes mixing the second hydrogel component with a solution containing exosomes to obtain a second hydrogel component loaded with exosomes.
[0044]
[10] The method according to [8] or [9], wherein after the step of preparing the carrier scaffold, it further comprises a step of loading the carrier scaffold with an antimicrobial peptide, wherein the carrier scaffold is immersed in a solution containing the antimicrobial peptide to obtain the carrier scaffold loaded with the antimicrobial peptide;
[0045] Preferably, in the solution containing the antimicrobial peptide, the concentration of the antimicrobial peptide is 0.1-10 mg / mL.
[0046]
[11] Any of the following uses of the composite hydrogel coaxial scaffold prepared by the composite hydrogel coaxial scaffold according to any one of [1] to [8] or the preparation method described in any one of [9] to
[10] :
[0047] (i) Use in the preparation of biological transplant materials;
[0048] (ii) Use in the preparation of products for bone repair;
[0049] (iii) Use in the preparation of bone regeneration products.
[0050]
[12] The use according to
[11] , wherein the biological transplant material is a biological transplant material used in the alveolar socket after tooth extraction; or
[0051] The bone repair product is a bone repair product used to fill the alveolar socket after tooth extraction; or
[0052] The bone regeneration product is a bone regeneration product used for filling the alveolar socket after tooth extraction.
[0053] Effects of the Invention
[0054] In some embodiments of the present invention, a three-dimensional scaffold is prepared by incorporating an osteogenic inductive component (e.g., hydroxyapatite (HA)) into a gel (e.g., SIS hydrogel), and the osteogenic inductive component (e.g., HA) is fused with the collagen in the gel (e.g., SIS hydrogel), effectively balancing the high mechanical strength of the inorganic component and the unique flexibility of the organic component. By mimicking the bone structure, the scaffold is designed to have a cavity structure (e.g., a hollow structure) to provide a deformable space, and at the same time, a gel (e.g., SIS hydrogel) is injected into the hollow part of the scaffold as the inner core of the scaffold. By cleverly utilizing the soft properties of the hydrogel, the composite hydrogel coaxial scaffold has excellent shaping ability while maintaining good mechanical strength and can flexibly fill the tooth extraction socket.
[0055] In some embodiments of the present invention, exosomes (e.g., BMSCs-Exos) are encapsulated in a gel (e.g., SIS hydrogel) inside the scaffold as the inner core of the scaffold, which can not only protect the exosomes from degradation, but also achieve local stable and continuous delivery, promote the migration and proliferation of BMSCs and HUVECs into the scaffold, and achieve vascularization and stable osteogenesis inside the scaffold.
[0056] In some embodiments of the present invention, antimicrobial peptides (such as GL13K) loaded on the stent can prevent infection at the implantation site and promote cell adhesion and proliferation, which is beneficial to angiogenesis and bone tissue reconstruction in the peripheral area of the stent.
[0057] The present invention cleverly utilizes the spatial structure of the scaffold, uses a gel / osteoinductive component scaffold loaded with antimicrobial peptides (such as GL13K) as the outer layer, and a gel (such as SIS hydrogel) loaded with exosomes (such as BMSC-Exos) as the inner core of the scaffold, and successfully prepares a coaxial scaffold material with certain shaping ability and good mechanical strength. This unique scaffold structure not only has excellent biocompatibility and antibacterial properties, but also can recruit cells to migrate into the scaffold, promoting angiogenesis and osteogenic differentiation in the inner and outer layers of the scaffold. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1A-1I Characteristics of BMSCs-derived exosomes are shown.
[0059] Figure 1A A schematic diagram of exosome synthesis is shown; Figure 1B Representative TEM images of BMSCs-derived exosomes are shown; Figure 1C The size and particle concentration of BMSCs-Exos were displayed using NTA; Figure 1D The distribution and intensity of exosomes are shown; Figure 1E Western blot analysis of the expression of Alix, CD63, CD9, and cytochrome C in BMSCs-Exos is shown; Figure 1F shows the CLSM images of SIS hydrogel loaded with BMSCs-Exos (Exos were labeled with DiI); Figure 1G The release profiles of Exos in SIS gel-Exos and SIS / HA+gel-Exos scaffolds are shown; Figure 1H The internalization of DiI-labeled Exos by HUVECs at 24 and 48 h is shown; Fig. 1I The internalization of DiI-labeled Exos by BMSCs at 24 and 48 hours is shown, with the cell nucleus shown in blue and the Exos shown in red.
[0060] Figure 2A-2K The preparation of composite hydrogel coaxial scaffolds and the characterization of different scaffolds are shown.
[0061] Figure 2A A schematic diagram showing the preparation of a composite hydrogel coaxial stent according to an embodiment; Figure 2B The rough appearance of different scaffolds is shown: (a) SIS / HA scaffold, (b) SIS gel, (c) hollow SIS / HA scaffold, and (d) SIS / HA+gel scaffold; Figure 2C Scanning electron microscopy images of SIS / HA, SIS gel, SIS / HA+gel, and G-SIS / HA+gel-Exos scaffolds are shown; Figure 2D Micro CT images of SIS / HA, SIS gel, SIS / HA+gel, and G-SIS / HA+gel-Exos scaffolds are shown; Figure 2E Compression deformation images of SIS / HA and SIS / HA+gel scaffolds are shown; Figure 2F Fourier transform infrared spectra of SIS / HA, SIS gel, SIS / HA+gel, and G-SIS / HA+gel-Exos scaffolds are shown; Figure 2GThe release images of GL13K in the coaxial scaffold observed by CLSM are shown, and GL13K is labeled with FITC (green); Figure 2H The degradation curves of SIS / HA, SIS gel, SIS / HA+gel, and G-SIS / HA+gel-Exos scaffolds are shown; Fig.2I The stress-strain curves of SIS / HA, SIS gel, and SIS / HA+gel scaffolds are shown; Figure 2J The porosity of SIS / HA, SIS gel, and SIS / HA+gel scaffolds is shown; Figure 2K The fluorescence intensity quantification of GL13K on G-SIS / HA+gel-Exos scaffolds is shown. Data are presented as standard deviation ± mean, n=3, *P<0.05, **P<0.01, ***P<0.001.
[0062] Figure 3A-3H The proliferation, migration, and morphology of cells on different scaffolds are shown.
[0063] Figure 3A A schematic diagram of cell behavior on the G-SIS / HA+gel-Exos scaffold is shown; Figure 3B The cell viability of BMSCs and HUVECs based on different scaffolds at 1, 3, 5, and 7 days is shown; Figure 3C Live and dead staining images of BMSCs and HUVECs cultured with different scaffold extracts (3 days) are shown; Figure 3D Migration staining of BMSCs and HUVECs by different scaffold extracts is shown; Figure 3E BMSCs and Figure 3F The migration number of HUVECs is shown (statistical analysis was performed using one-way ANOVA, data are expressed as mean ± standard deviation, *P < 0.05, **P < 0.01, ***P < 0.001); Figure 3G BMSCs and Figure 3H The cytoskeletal morphology of HUVECs after 3 days of culture is shown, including the nucleus (blue) and actin filaments (red).
[0064] Figure 4A-4G The scaffolds were shown to promote angiogenesis in vitro.
[0065] Figure 4A It shows that HUVECs formed microtubules after culturing on Matrigel for 6 h; Figure 4B Western blot analysis of the expression of angiogenesis-related proteins (HIF-1α and VEGF) is shown; Figure 4CQuantitative analysis of Western blot experiments is shown (data are expressed as mean ± SD, *P < 0.05, **P < 0.01, ***P < 0.001); Figure 4D and Figure 4E Immunofluorescence observation of the expression of angiogenesis-related proteins HIF-1α and VEGF is shown; Figure 4F Quantitative analysis of fluorescence intensity is shown (data are expressed as mean ± SD, *P < 0.05, **P < 0.01, ***P < 0.001); Figure 4G The expressions of angiogenesis-related genes HIF-1α and VEGF are shown (data are expressed as mean±standard deviation, *P<0.05, **P<0.01, ***P<0.001).
[0066] Figure 5A-5E In vitro osteogenic differentiation studies are shown.
[0067] Figure 5A ALP staining images of different scaffolds at 7 and 14 days are shown; Figure 5B ARS staining images of different scaffolds at 14 and 21 days are shown; Figure 5C Western blot analysis of the expression of osteogenic-related proteins (BMP2, ALP, OPN, and RUNX2) is shown; Figure 5D Quantitative analysis of Western blot analysis is shown (data are expressed as mean ± SD, *P < 0.05, **P < 0.01, ***P < 0.001); Figure 5E The expression levels of osteogenesis-related genes (ALP, BMP2, OPN, RUNX2) detected by qRT-PCR are shown (data are expressed as mean ± standard deviation, *P < 0.05, **P < 0.01, ***P < 0.001).
[0068] Figure 6 Immunofluorescence staining of osteogenesis-related proteins was performed to observe the expression of osteogenesis-related proteins and to perform quantitative analysis of fluorescence intensity (ALP, BMP2, RUNX2).
[0069] Figure 7A-7E Showed antibacterial activity in vitro.
[0070] Fig. 7A SEM images are shown; Figure 7B Plate counts of bacterial colonies (Sa, Ss, and Fn) are shown; Figure 7C Colony quantification analysis is shown; Fig.7D CLSM images of Sa, Ss, and Fn live / dead staining are shown (green: live bacteria, red: dead bacteria); Fig. 7EThe inhibition zones and statistical analysis of the inhibition zones of Sa, Ss, and Fn co-cultured with different scaffolds are shown (a: SIS / HA+gel, b: G-SIS / HA+gel, c: SIS / HA+gel-Exos, d: G-SIS / HA+gel-Exos).
[0071] Figure 8A-8H Evaluation and analysis after tooth extraction and dentoalveolar reconstruction are shown.
[0072] Fig. 8A Schematic diagram of the experiment after tooth extraction and alveolar reconstruction is shown; Figure 8B Colony counts at the wound site are shown; Figure 8C Sagittal views of the rat maxilla are shown; Fig.8D The micro-CT horizontal images of the right maxillary alveolar bone of the rat are shown; Fig. 8E Micro-CT three-dimensional reconstruction of rat alveolar bone defect is shown; Figure 8F Quantitative analysis of bone mineral density (BMD), bone volume fraction (BV / TV) and trabecular thickness are shown (data are expressed as mean ± standard deviation, *P<0.05, **P<0.01, ***P<0.001); Figure 8G HE staining and Masson's trichrome staining were shown to evaluate the new bone tissue 1 month after surgery; Figure 8H Immunofluorescence staining of CD34 and OCN is shown.
[0073] Fig. 9 The structure and application of an embodiment of a SIS / HA composite hydrogel coaxial scaffold are shown. DETAILED DESCRIPTION
[0074] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0075] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0076] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0077] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0078] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0079] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0080] In addition, in this specification, the "water" includes any feasible water that can be used, such as deionized water, distilled water, ion exchange water, double distilled water, high-purity water, and pure water.
[0081] According to the present disclosure, the terms "polypeptide", "protein" and "peptide" are used interchangeably herein to refer to a polymeric form of amino acids of any length, which may include coded and non-coded amino acids, chemically or biochemically modified or derivatized amino acids, and polypeptides with similar peptide backbones.
[0082] According to the present disclosure, the term "amino acid" may include natural amino acids, unnatural amino acids, amino acid analogs and all their D and L stereoisomers. According to the present disclosure, the amino acid three-letter code and one-letter code used are as described in J.biol.chem, 243, p3558 (1968). The amino acids and their abbreviations and English abbreviations in the present disclosure are as follows: histidine (His, H); serine (Ser, S); glutamic acid (Glu, E); glutamine (Gln, Q); glycine (Gly, G); threonine (Thr, T); phenylalanine (Phe, F); aspartic acid (Asp, D); tyrosine (Tyr, Y); leucine (Leu, L); isoleucine (Ile, I); arginine (Arg, R); alanine (Ala, A); valine (Val, V); tryptophan (Trp, W); methionine (Met, M); asparagine (Asn, N); cysteine (Cys, C); lysine (Lys, K); proline (Pro, P).
[0083] As used in the present disclosure, "conservative substitutions" generally exchange an amino acid at one or more sites in a protein. Such substitutions may be conservative. Specifically, substitutions considered to be conservative substitutions include substitutions of Ala to Ser or Thr, substitutions of Arg to Gln, His or Lys, substitutions of Asn to Glu, Gln, Lys, His or Asp, substitutions of Asp to Asn, Glu or Gln, substitutions of Cys to Ser or Ala, substitutions of Gln to Asn, Glu, Lys, His, Asp or Arg, substitutions of Glu to Gly, Asn, Gln, Lys or Asp, substitutions of Gly to Pro, substitutions of His to Asn, Lys, Gln, Arg or Tyr. Conservative mutations include substitutions of Ile to Leu, Met, Val or Phe, substitutions of Leu to Ile, Met, Val or Phe, substitutions of Lys to Asn, Glu, Gln, His or Arg, substitutions of Met to Ile, Leu, Val or Phe, substitutions of Phe to Trp, Tyr, Met, Ile or Leu, substitutions of Ser to Thr or Ala, substitutions of Thr to Ser or Ala, substitutions of Trp to Phe or Tyr, substitutions of Tyr to His, Phe or Trp, and substitutions of Val to Met, Ile or Leu. In addition, conservative mutations also include naturally occurring mutations caused by individual differences, strains, species differences, etc. from which genes are derived.
[0084] As used in this disclosure, "HA" means hydroxy apatite.
[0085] As used in the present disclosure, "BMSC" or "BMSCs" means Bone Marrow Mesenchymal Stem Cells.
[0086] As used in this disclosure, "HUVEC" or "HUVECs" means Human Umbilical Vein Endothelial Cells.
[0087] As used in this disclosure, "BMP2" means Bone Morphogenetic Protein-2.
[0088] As used in this disclosure, "ALP" means Alkaline Phosphatase.
[0089] As used in this disclosure, "OPN" means osteopontin.
[0090] As used in this disclosure, "RUNX2" means Runt-related transcription factor 2.
[0091] As used in this disclosure, "VEGF" stands for Vascular Endothelial Growth Factor.
[0092] As used in this disclosure, "HIF-1α" means Hypoxia-inducible factor 1-alpha.
[0093] As used in this disclosure, "OCN" means osteocalcin.
[0094] <First aspect>
[0095] The first aspect of the present invention provides a composite hydrogel coaxial stent, comprising:
[0096] A carrier scaffold, the carrier scaffold comprising a scaffold body having a cavity formed by a gel mixture, wherein the gel mixture comprises a first hydrogel component and an osteogenic induction component; and
[0097] The inner core is filled in the cavity of the carrier support, and the inner core comprises a second hydrogel component.
[0098] The composite hydrogel coaxial scaffold of the present invention prepares a three-dimensional scaffold by incorporating an osteogenic induction component into a first hydrogel component, and the osteogenic induction component is fused with the hydrogel component, effectively balancing high mechanical strength and flexibility. By biomimetic bone structure, the scaffold is designed to have a cavity structure, providing a deformable space, and at the same time, the second hydrogel component is injected into the cavity part of the scaffold as the inner core of the scaffold. By cleverly utilizing the soft properties of the hydrogel, the composite hydrogel coaxial scaffold maintains good mechanical strength while also having excellent shaping ability and can flexibly fill the tooth extraction socket.
[0099] Carrier support
[0100] In some embodiments, the carrier scaffold includes a scaffold body having a cavity formed by a gel mixture, and the gel mixture includes a first hydrogel component and an osteoinductive component.
[0101] (First hydrogel component)
[0102] As for the selection of the gel of the first hydrogel component, the present invention can use one or a combination of two or more of porcine small intestinal submucosal gel, alginate, hyaluronic acid, collagen and the like, which have good biocompatibility.
[0103] Porcine small intestinal submucosa (SIS) gel is an extracellular matrix hydrogel with good biocompatibility. It retains many functional proteins and bioactive factors in natural tissues, is beneficial to tissue repair and reconstruction, and is an ideal tissue regeneration material. Therefore, the present invention preferably uses porcine small intestinal submucosa gel as the gel.
[0104] Alginate reacts with multivalent cations (except magnesium ions) to form cross-linked bonds between macromolecules. When the content of multivalent cations increases, the alginate solution becomes more and more viscous, and finally forms a gel and produces a precipitate. For example, by using a Ca-containing 2+ Preferably, in the present invention, alginate can be prepared by mixing with Ca 2+ The solution cross-links to form a gel. 2+ After the rheological properties are lost due to cross-linking under the action of , the flow of water molecules is inhibited, and an alginate gel with extremely high water content is produced. The gel is not thermally reversible and has good stability.
[0105] In the present invention, hyaluronic acid gel with a three-dimensional network structure can also be used as the gel. Specifically, other cross-linking agents, adjuvants or drugs can be added as needed during the preparation of the hyaluronic acid gel to achieve a specific drug sustained release effect.
[0106] In some preferred embodiments, the gel of the first gel component of the gel mixture of the carrier scaffold comprises porcine small intestinal submucosal gel, which is referred to as SIS gel or SIS hydrogel. In the gel mixture, a scaffold prepared by incorporating an osteogenic induction component (such as hydroxyapatite) into the SIS gel, such as a SIS / HA three-dimensional scaffold, HA is fused with collagen in the SIS gel, effectively balancing the high mechanical strength of the inorganic component and the unique flexibility of the organic component.
[0107] (Osteogenic Induction Component)
[0108] In the present invention, the osteoinductive component is selected from one or a combination of two or more of hydroxyapatite, tricalcium phosphate, tetracalcium phosphate, octacalcium phosphate, calcium oxide, calcium silicate, calcium sulfate or calcium carbonate, but is not limited thereto.
[0109] In some preferred embodiments, the osteoinductive component comprises hydroxyapatite.
[0110] In some more preferred embodiments, the hydroxyapatite particles have a particle size of 0.1-0.15 mm. The hydroxyapatite particles have a regular morphology, a flat surface, and consistent particle shape and size, are less likely to cause immune response or foreign body reaction, and are less irritating to human tissues, and therefore have better biocompatibility in vivo.
[0111] In some embodiments, the carrier scaffold has a cavity, so that the scaffold has a deformable space, mimicking the bone structure.
[0112] In some embodiments, the carrier scaffold has an interconnected porous network structure with a porosity of 67% to 85%, preferably 70% to 80%, for example 75%. At this porosity, the gel is present in the porous network structure of the carrier scaffold, so the scaffold is conducive to promoting bone tissue regeneration and repair, and can also provide good mechanical strength and stability, so that the composite hydrogel coaxial scaffold can be used for bone tissue engineering materials. Moreover, at this porosity, it is conducive to the release of exosomes and antimicrobial peptides from the composite hydrogel coaxial scaffold of the present invention, and achieve local stable and continuous delivery.
[0113] In some embodiments, in the carrier scaffold, the mass ratio of the first hydrogel component to the osteoinductive component is 1:(5-15). In some preferred embodiments, the mass ratio of the first hydrogel component to the osteoinductive component is 1:(7-13). In some more preferred embodiments, the mass ratio of the first hydrogel component to the osteoinductive component is 1:(8-12), for example, 1:8, 1:9, 1:10, 1:11 or 1:12. Under the above ratio, it is more conducive to the carrier scaffold to provide good mechanical strength and stability, and more effectively balance the high mechanical strength of the inorganic component and the unique flexibility of the organic component. And it is more conducive to the composite hydrogel coaxial scaffold of the present invention to release exosomes and antimicrobial peptides, and achieve local stable and continuous delivery.
[0114] Antimicrobial peptides
[0115] Unlike bone defects in other parts of the body, the oral cavity is a complex dynamic micro-ecological system that is in direct contact with the outside world and is home to a diverse microbial community. Given the complexity of the oral environment, it is critical to prevent stent implant infection. The carrier stent of the present invention is loaded with antimicrobial peptides to inhibit bacteria, such as Staphylococcus aureus, Escherichia coli, and the like.
[0116] In some embodiments, the antimicrobial peptide comprises a cationic antimicrobial peptide.
[0117] In some preferred embodiments, the antimicrobial peptide comprises the amino acid sequence shown in SEQ ID NO: 1, or an amino acid sequence having one, two, three, four or five conservative substitutions compared to the amino acid sequence shown in SEQ ID NO: 1.
[0118] Specifically, the antimicrobial peptide of the present invention is GL13K (GKIIKLKASLKLL-CONH2; SEQ ID NO: 1), which is derived from a human parotid gland secretory protein and is a short cationic antimicrobial peptide composed of 13 amino acids.
[0119] In this specification, an amide functional group refers to a functional group formed by a carboxyl group (-COOH) and an amino group (-NH2) on a nitrogen atom, with a structural formula of -CONH2, also known as an amide group. The amide functional group has strong basicity and acidity, and can react with acidic and basic substances to form salts. Therefore, the amide functional group is the most important neutral functional group in organic matter.
[0120] GL13K has an inhibitory effect on common bacteria, such as Staphylococcus aureus and Escherichia coli, and also has excellent antibacterial effects on Porphyromonas gingivalis and Fusobacterium nucleatum, which are common in the oral environment. In addition, GL13K can promote the proliferation and adhesion of HUVECs and BMSCs, upregulate the expression of genes and proteins related to osteogenesis and angiogenesis, and promote angiogenesis and osteogenic differentiation. Therefore, loading GL13K on the scaffold can prevent infection at the implantation site and promote angiogenesis and bone tissue reconstruction.
[0121] In some embodiments, per 1 mg of the carrier scaffold, more than 1 μg of the antimicrobial peptide is loaded, preferably more than 2 μg of the antimicrobial peptide, and more preferably more than 4 μg of the antimicrobial peptide.
[0122] In some specific embodiments, 1-10 μg of antimicrobial peptide is loaded per 1 mg of the carrier scaffold, preferably 2-10 μg of antimicrobial peptide is loaded, and more preferably 4-10 μg of antimicrobial peptide is loaded. In the present invention, the antimicrobial peptide is more conducive to the antimicrobial effect of the antimicrobial peptide within the above range, and is more conducive to its role in promoting angiogenesis and osteogenic differentiation.
[0123] Inner core
[0124] In some embodiments, the inner core fills the cavity of the carrier scaffold, and the inner core comprises a second hydrogel component.
[0125] The present invention cleverly utilizes the soft properties of the gel component in the inner core and combines it with a carrier stent, so that the composite hydrogel coaxial stent of the present invention has excellent shaping ability while maintaining good mechanical strength and can flexibly fill the tooth extraction socket.
[0126] As for the selection of the gel of the second gel component, the present invention can use one or a combination of two or more gels with good biocompatibility such as porcine small intestinal submucosal gel, alginate, hyaluronic acid, collagen, etc. The above gel has been described in detail in the "first hydrogel component" in the "carrier scaffold" section, and will not be repeated here.
[0127] In some embodiments, the first gel component is the same as the second gel component. In other embodiments, the first gel component is different from the second gel component.
[0128] In some preferred embodiments, the gel in the inner core comprises porcine small intestinal submucosa gel.
[0129] In some specific embodiments, in the composite hydrogel coaxial stent of the present invention, the carrier stent is substantially coaxial with the inner core. For example, the carrier stent is a substantially cylindrical structure with a cavity (e.g., hollow), and the inner core located in the cavity of the carrier stent is substantially cylindrical, so that the carrier stent is coaxial with the inner core to form a coaxial stent.
[0130] exosomes
[0131] Cell homing is a key process in tissue repair. Attracting endogenous stem cells from the host to the defect site can eliminate the need to obtain cells in vitro and achieve in situ bone regeneration in the alveolar socket. However, in most cases, scaffold materials are placed in bone defects, and the direction of bone tissue reconstruction usually grows from the edge of the defect to the center. There is less bone formation in the center of the defect, which may be attributed to the limited migration and proliferation of cells into the scaffold.
[0132] In some embodiments, the second hydrogel component of the inner core is loaded with exosomes.
[0133] "Exosomes (EVs or Exosomes, Exos)" refer to vesicles with double membrane structures produced by cells through paracrine pathways, with diameters ranging from 40nm to 1000nm. Exosomes are widely present in cell culture supernatants and various body fluids (blood, lymph, saliva, urine, semen, and milk), carrying a variety of proteins, lipids and other substances related to cell sources, and participating in processes such as intercellular communication, cell migration, angiogenesis, and immune regulation. In some specific embodiments, exosomes are derived from mesenchymal stem cells, more preferably from bone marrow mesenchymal stem cells (BMSC).
[0134] In some preferred embodiments, the exosomes are exosomes derived from bone marrow mesenchymal stem cells (BMSCs-Exos). BMSCs-Exos play an important role in inducing osteogenic differentiation and bone regeneration of BMSCs, can effectively activate the bone tissue repair process, promote cell survival, proliferation and osteogenic differentiation, and have a positive effect on the healing and reconstruction of bone defects.
[0135] Wrapping BMSCs-Exos in the gel inside the carrier scaffold as the inner core of the carrier scaffold can not only protect Exos from degradation, but also achieve local stable and continuous delivery, promote the migration and proliferation of BMSCs and HUVECs into the scaffold, and achieve vascularization and stable osteogenesis inside the scaffold. The inventors of the present invention have found that by loading BMSCs-Exos in a hydrogel and implanting them in vivo, the host's endogenous stem cells can be attracted to the defect site, eliminating the need to obtain cells in vitro and achieving bone regeneration.
[0136] <Second Aspect>
[0137] The second aspect of the present invention provides a method for preparing the composite hydrogel coaxial scaffold according to the first aspect of the present invention, comprising the following steps:
[0138] a step of preparing a carrier scaffold, wherein the osteogenic induction component is mixed with the first hydrogel component, added to a mold, and dried to obtain a carrier scaffold having a cavity; and
[0139] The step of filling the inner core is to fill the second hydrogel component into the cavity of the carrier stent to form a composite hydrogel coaxial stent.
[0140] Steps for preparing carrier scaffolds
[0141] (First hydrogel component)
[0142] As for the gel of the first hydrogel component, any feasible gel with good biocompatibility such as porcine small intestinal submucosal gel, alginate and hyaluronic acid can be used in the present invention. It can be prepared by conventional methods or purchased.
[0143] Taking the porcine small intestinal submucosal gel as an example, its preparation method is as follows:
[0144] Take fresh pig small intestine, remove the mucosal layer and muscular layer, and obtain the submucosa of pig small intestine;
[0145] Pre-treating the pig small intestinal submucosa to obtain a pre-treated product;
[0146] hydrolyzing the pretreated product by using a protease to obtain a hydrolyzate;
[0147] Optionally, the hydrolyzate is neutralized to obtain porcine small intestinal submucosal gel, namely, SIS gel.
[0148] The pretreatment may include defatting, digestion, washing, disinfection, etc. The present invention does not specifically limit the above steps, and the treatment may be performed according to the commonly used methods in the art.
[0149] For degreasing treatment, a mixed solution of methanol and chloroform can generally be used for degreasing treatment, the volume ratio of methanol to chloroform can be 1:0.5-2, and the degreasing treatment time can be 6-18 hours.
[0150] For digestion treatment, a mixture of a protease solution with a mass concentration of 0.01-0.1% and a chelating agent solution with a mass concentration of 0.01-0.1% can generally be used for digestion treatment, and the digestion treatment time can be 6-18 hours.
[0151] For washing treatment, a detergent can be used for washing. The detergent can be a mixed solution of sodium dodecyl sulfate and sodium chloride. Specifically, sodium dodecyl sulfate with a mass concentration of 0.1-3% and sodium chloride with a mass concentration of 0.3-5% can be mixed. The washing treatment time can be 1-8 hours.
[0152] For disinfection, peroxide and / or ethanol may be used for disinfection, and the disinfection time may be 10-60 minutes.
[0153] The protease may be an acidic protease, a neutral protease, an alkaline protease, etc. The present invention does not particularly limit the type of the protease, as long as the gel of the present invention can be prepared. In the present invention, it is preferred to use an acidic protease for treatment, such as pepsin, etc.
[0154] When the pre-treated product is hydrolyzed by acidic protease, an acidic substance, such as acetic acid, can be used to adjust the pH of the pre-treated product to be acidic. The present invention does not specifically limit the pH value, as long as it is the optimal pH value for the acidic protease.
[0155] When the pre-treated product is hydrolyzed by acidic protease, the hydrolyzate can be neutralized by alkaline substances. After neutralization, it is incubated in an incubator at 37 degrees Celsius for 30 minutes to obtain a porcine small intestinal submucosal hydrogel, namely, SIS hydrogel.
[0156] (Osteogenic Induction Component)
[0157] In some embodiments, the osteoinductive component is as described above in the "osteoinductive component" of the first aspect.
[0158] In some specific embodiments, the step of preparing the carrier scaffold comprises the following steps:
[0159] adding the osteoinductive component to the first hydrogel component and stirring to obtain a gel mixture (i.e., a mixture of the first hydrogel component and the osteoinductive component);
[0160] The gel mixture is poured into a mold and freeze-dried to obtain a carrier scaffold.
[0161] In some embodiments, the first hydrogel component is neutral, ie, the first hydrogel component has a pH of 7.2 ± 0.2.
[0162] In some embodiments, the osteoinductive component is added to the first hydrogel component with stirring at low temperature, which refers to about a 4°C water bath, to prevent premature gelation.
[0163] The mold material can be silicone, metal mold, plaster mold, rubber mold, etc. The present invention does not specifically limit the material of the mold, as long as the stent of the present invention can be prepared. In the present invention, a silicone mold is preferably used.
[0164] The shape of the mold can be cylindrical, square, rectangular, circular, tubular or other hollow shapes. The present invention does not specifically limit the shape of the mold, as long as the stent of the present invention can be prepared. In the present invention, a tubular hollow silicone mold is preferably used.
[0165] For the drying treatment, vacuum drying, freeze drying, room temperature drying, etc. can be used. The present invention does not specifically limit the method of drying treatment, as long as the stent of the present invention can be prepared. In the present invention, freeze drying is preferably used, for example, freezing at about -20°C for about 24 hours, and freeze drying at -80°C using a freeze dryer. The freeze-dried material maintains the original chemical composition and physical properties (such as porous structure).
[0166] (Carrier scaffold loaded with antimicrobial peptides)
[0167] In some preferred embodiments of the present invention, after the step of preparing the carrier scaffold, the method further comprises the step of loading the carrier scaffold with antimicrobial peptides, wherein the carrier scaffold is immersed in a solution containing the antimicrobial peptides to obtain the carrier scaffold loaded with the antimicrobial peptides.
[0168] In some embodiments, in the solution containing antimicrobial peptides, the concentration of the antimicrobial peptides is 0.1-10 mg / mL. In some preferred embodiments, in the solution containing antimicrobial peptides, the concentration of the antimicrobial peptides is 0.1-10 mg / mL, preferably 0.3-7 mg / mL, more preferably 0.5-5 mg / mL, for example 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, further preferably 0.5-2 mg / mL, further preferably 1-2 mg / mL.
[0169] At this concentration, the peptide can be effectively loaded on the scaffold in maximum amount and released for long term bone repair.
[0170] In the present invention, concentration gradients of 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, and 2 mg / mL were set to immerse the scaffold, and the scaffold loaded with antimicrobial peptides was observed by fluorescence microscopy. The fluorescence intensity and density of 1 mg / mL and 2 mg / mL were similar. Therefore, by immersing the scaffold in an antimicrobial peptide solution with a concentration of about 1 mg / mL, the peptide can be effectively loaded on the scaffold in the maximum amount and released for a long time to perform bone repair.
[0171] In some specific embodiments, for the GL13K antimicrobial peptide, its minimum inhibitory concentration against Streptococcus, Fusobacterium nucleatum and Escherichia coli is less than 100 μg / mL, and selecting about 1 mg / mL can effectively exert the antibacterial effect and maintain a favorable osteogenic and angiogenic environment.
[0172] The immersion method can be multiple immersion methods, percolation methods, liquid immersion methods, barrel leaching methods, and liquid injection methods. The present invention is not particularly limited, as long as the stent loaded with GL13K antimicrobial peptide described in the present invention can be prepared. In some embodiments, the immersion time can be 10-60 minutes, preferably 20-50 minutes, for example 20 minutes, 30 minutes, 40 minutes, 50 minutes.
[0173] Under the above-mentioned antimicrobial peptide concentration and immersion time conditions, the antimicrobial peptide can be effectively loaded on the carrier scaffold, and when the composite hydrogel coaxial scaffold of the present invention is subsequently used, it can effectively exert an antimicrobial effect, promote angiogenesis and osteogenic differentiation, etc.
[0174] For washing the surface of the carrier support after immersion, water, buffer solution, etc. can be used as the mobile phase. In the present invention, PBS buffer solution is preferably used for washing.
[0175] The carrier stent is dried after immersion by vacuum drying, freeze drying, room temperature drying, etc. The present invention does not specifically limit the drying method, as long as the stent described in the invention can be prepared. In the present invention, ventilation drying at room temperature is preferably used.
[0176] Steps for filling the core
[0177] In the present invention, the second hydrogel component is filled into the cavity of the carrier stent to form a composite hydrogel coaxial stent.
[0178] As for the gel of the second hydrogel component, any feasible gel with good biocompatibility such as porcine small intestinal submucosal gel, alginate and hyaluronic acid can be used in the present invention. It can be prepared by conventional methods or purchased.
[0179] Taking the porcine small intestinal submucosal gel as an example, its preparation method is as described in the above section "Steps for Preparing Carrier Scaffolds".
[0180] In some preferred embodiments, in the step of filling the inner core, the second hydrogel component is a second hydrogel component loaded with exosomes. In these embodiments, before the step of filling the inner core, a step of loading the gel with exosomes is included, which includes mixing the second hydrogel component with a solution containing exosomes to obtain a gel loaded with exosomes.
[0181] The method for preparing the exosomes in the present invention can be sucrose cushion density gradient centrifugation, ultracentrifugation, polyethylene glycol precipitation, etc. The present invention is not particularly limited to the method for preparing exosomes, as long as the exosomes described in the present invention can be prepared. In the present invention, ultracentrifugation is preferably used for processing.
[0182] When ultracentrifugation is used to extract exosomes, the solution can be filtered through a 0.22 μm filter and then centrifuged to retain the precipitate as exosomes.
[0183] The solution containing exosomes and the pregel are mixed to obtain the material of the inner core. The present invention does not specifically limit the mixing method, and the mixing can be performed in a conventional manner.
[0184] In the present invention, the gel or the gel loaded with exosomes is filled into the stent to obtain a composite hydrogel coaxial stent. The present invention does not specifically limit the filling method, and the filling can be performed in a conventional manner.
[0185] <Third Aspect>
[0186] The third aspect of the present invention provides any of the following uses of the composite hydrogel coaxial scaffold described in the first aspect of the present invention or the composite hydrogel coaxial scaffold prepared by the preparation method described in the second aspect of the present invention:
[0187] (i) Use in the preparation of biological transplant materials;
[0188] (ii) Use in the preparation of products for bone repair;
[0189] (iii) Use in the preparation of bone regeneration products.
[0190] In some specific embodiments, the biograft material is a biograft material used in the alveolar socket after tooth extraction.
[0191] In some specific embodiments, the bone repair product is a bone repair product for filling a post-tooth extraction alveolar socket.
[0192] In some specific embodiments, the bone regeneration product is a bone regeneration product for filling the alveolar socket after tooth extraction.
[0193] The present invention combines gel with a coaxial hollow stent, which has certain mechanical strength and plasticity, can adaptively fill the tooth extraction socket and retain the three-dimensional bone formation space. The exosomes (BMSCs-Exos) in the inner layer of the composite hydrogel coaxial stent material of the present invention can effectively promote the proliferation and migration of human umbilical vein endothelial cells (HUVECs) and BMSCs into the stent, upregulate the expression of genes related to osteoblasts (BMP2, ALP, RUNX2 and OPN) and angiogenesis (HIF-1α and VEGF), induce angiogenesis and osteogenic differentiation inside the stent, and improve the problem of low bone formation rate in the center of the defect. In addition, the release of antimicrobial peptides at the periphery of the stent exerts a local antibacterial effect, ensures a favorable osteogenic environment, and further promotes vascularization and new bone formation in the peripheral area. This design aims to achieve a comprehensive and efficient bone repair effect on the alveolar socket after tooth extraction using a coaxial stent through a dual internal and external mechanism.
[0194] Example
[0195] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0196] Preparation Example: Preparation of Gel and Scaffold Used in Test Example
[0197] Preparation Example 1: Composite hydrogel coaxial scaffold GL13K-SIS / HA+gel-Exos (abbreviated as: GL13K-SIS / HA+ Preparation of gel-Exos or G-SIS / HA+gel-Exos
[0198] See also Figure 2A :
[0199] 1. The process of obtaining the small intestinal submucosa (SIS) includes mechanically removing the mucosa and seromuscular layer of fresh porcine small intestine, and then washing with deionized water for 3-5 times. After washing, degreasing for 12 hours (methanol and chloroform v / v=1:1), digesting with 0.05% (mass volume ratio, g / mL) trypsin / 0.05% (mass volume ratio, g / mL) EDTA for 12 hours, washing with detergent (0.5% sodium dodecyl sulfate in 0.9% sodium chloride) for 4 hours, sterilizing with 0.1 (v / v)% peracetic acid and 20 (v / v)% ethanol for 30 minutes, drying and mincing at room temperature. Then, 1g SIS was immersed in 100mL 0.5mol / L acetic acid solution, and 50mg pepsin was added for stirring enzymolysis for 48 hours. After centrifugation, acidic SIS pre-gel (pre-gel; 10% w / v) was obtained. The pregel was adjusted to neutrality (pH=7.2±0.2) with NaOH solution to obtain neutral SIS pregel.
[0200] 2. Bone marrow mesenchymal stem cells (BMSCs) were cultured in a culture dish containing DMEM, 10% Exos-free fetal bovine serum and 1% penicillin and streptomycin at 37°C and 5% CO2. The supernatant was collected to separate exosomes. First, the cell debris was removed by centrifugation at 1000g for 30 minutes and 12000g for 60 minutes at 4°C. The supernatant was then filtered with a 0.22μm filter (Solarbio, China). Subsequently, the precipitate was obtained by centrifugation at 100,000g for 90 minutes. Finally, the precipitate was washed with PBS and centrifuged at 100,000g for 1h to obtain Exos, which can be stored at -80°C for future use.
[0201] 3. Mix 200 μL of neutral SIS pre-gel in step 1 with 100 μL of Exos solution (Exos obtained in step 2 are resuspended in PBS to obtain Exos solution, and the solution is detected by nanoparticle size analyzer.
[0202] 3.29×10 8 particles / mL; the exosome concentration detected by an ELISA reader was 1.16 μg / μL) and mixed at 4°C to prepare SIS pre-gel loaded with Exos.
[0203] 4. Stir HA particles into the neutral SIS pregel in step 1 at low temperature (4°C water bath) to form a mixture, wherein the mass ratio of HA particles to SIS pregel is 9:1, and then pour into a customized tubular mold and completely freeze-dry (freeze at -20°C for 24 hours and freeze-dry at -80°C) to obtain a hollow SIS / HA scaffold.
[0204] 5. The antimicrobial peptide GL13K was dissolved in deionized water to prepare a GL13K solution with a concentration of 1 mg / ml. The hollow SIS / HA scaffold obtained in step 4 was immersed in the GL13K solution for 30 minutes, rinsed three times with PBS buffer solution, and then dried under ventilation at room temperature (25±5°C) to obtain a hollow SIS / HA scaffold loaded with GL13K.
[0205] 6. Preparation of the composite hydrogel coaxial scaffold G-SIS / HA+gel-Exos was performed by extracting the Exos-loaded SIS pregel obtained in step 3 with a syringe and uniformly filling it into the hollow part of the hollow SIS / HA scaffold loaded with GL13K obtained in step 5. The scaffold was then placed at 37°C for 30 minutes to obtain the composite hydrogel coaxial scaffold G-SIS / HA+gel-Exos. The outer shell of the G-SIS / HA+gel-Exos scaffold was loaded with GL13K, while the inner core was the SIS hydrogel containing Exos, e.g. Figure 2A shown.
[0206] Preparation Example 2: Preparation of composite hydrogel coaxial scaffold SIS / HA+gel (abbreviated as: SIS / HA+gel)
[0207] 1. Stir HA particles into the neutral SIS pregel obtained according to the method of step 1 in Preparation Example 1 at low temperature (4°C in a water bath) to form a mixture, which is then poured into a customized tubular mold and completely freeze-dried (freeze at -20°C for 24 hours and freeze-dried at -80°C) to obtain a hollow SIS / HA scaffold.
[0208] 2. Preparation of the composite hydrogel coaxial scaffold SIS / HA+gel: The neutral SIS pregel obtained according to the method of step 1 in preparation example 1 was extracted with a syringe and uniformly filled into the hollow part of the hollow SIS / HA scaffold obtained in step 1. The scaffold was then placed at 37°C for 30 minutes to obtain a composite hydrogel coaxial scaffold SIS / HA+gel. Figure 2B as shown in (d).
[0209] Preparation Example 3: Preparation of composite hydrogel coaxial scaffold G-SIS / HA+gel
[0210] 1. Stir HA particles into the neutral SIS pregel obtained according to the method of step 1 in Preparation Example 1 at low temperature (4°C in a water bath) to form a mixture, which is then poured into a customized tubular mold and completely freeze-dried (freeze at -20°C for 24 hours and freeze-dried at -80°C) to obtain a hollow SIS / HA scaffold.
[0211] 2. Obtain GL13K solution according to the method in step 5 of preparation example 1. Immerse the hollow SIS / HA scaffold obtained in step 1 in the GL13K solution for 30 minutes, rinse with PBS three times, and then dry under ventilation at room temperature to obtain a hollow SIS / HA scaffold loaded with GL13K.
[0212] 3. The preparation of the composite hydrogel coaxial scaffold G-SIS / HA+gel is to extract the neutral SIS pre-gel obtained according to the method of step 1 in preparation example 1 with a syringe, and evenly fill it into the hollow part of the hollow SIS / HA scaffold loaded with GL13K obtained in step 2. Then the scaffold is placed at a temperature of 37°C for 30 minutes to obtain the composite hydrogel coaxial scaffold G-SIS / HA+gel.
[0213] Preparation Example 4: Preparation of composite hydrogel coaxial scaffold SIS / HA+gel-Exos (abbreviated as: SIS / HA+gel-Exos)
[0214] 1. Stir HA particles into the neutral SIS pregel obtained according to the method of step 1 in Preparation Example 1 at low temperature (4°C in a water bath) to form a mixture, which is then poured into a customized tubular mold and completely freeze-dried (freeze at -20°C for 24 hours and freeze-dried at -80°C) to obtain a hollow SIS / HA scaffold.
[0215] 2. Exos were obtained according to the method of step 2 in preparation example 1, and 100 μL of Exos solution (Exos obtained in step 2 of preparation example 1 were resuspended in PBS to obtain Exos solution, and the particle size was 3.29×10 8 particles / ml; the exosome concentration detected by the microplate reader was 1.16 μg / μL) and 200 μL of neutral SIS pre-gel obtained by the method of step 1 in Preparation Example 1 were mixed at 4°C to prepare SIS pre-gel loaded with Exos.
[0216] 3. The preparation of the composite hydrogel coaxial scaffold SIS / HA+gel-Exos is to extract the Exos-loaded SIS pregel obtained in step 2 with a syringe and evenly fill it into the hollow part of the hollow SIS / HA scaffold obtained in step 1. The scaffold is then placed at 37°C for 30 minutes to obtain a composite hydrogel coaxial scaffold SIS / HA+gel-Exos.
[0217] Preparation Example 5: Preparation of SIS / HA Scaffold (SIS / HA)
[0218] At low temperature (4°C in a water bath), HA particles were stirred into the neutral SIS pregel obtained according to the method of step 1 in Preparation Example 1 to form a mixture, which was then poured into a customized cylindrical mold and completely freeze-dried to obtain a solid SIS / HA scaffold, such as Figure 2B As shown in (a).
[0219] Preparation Example 6: Preparation of SIS hydrogel scaffold
[0220] The neutral SIS pregel obtained according to the method of step 1 in preparation example 1 was placed at 37° C. for 30 minutes to obtain a SIS hydrogel, such as Figure 2B as shown in (b).
[0221] Preparation Example 7: Preparation method of hollow SIS / HA (i.e., hollow SIS / HA scaffold)
[0222] At low temperature (4°C in a water bath), HA particles were stirred into the neutral SIS pregel obtained according to the method of step 1 in Preparation Example 1 to form a mixture, which was then poured into a custom tubular mold and completely freeze-dried to obtain a hollow SIS / HA scaffold, such as Figure 2B as shown in (c).
[0223] Preparation Example 8: SIS hydrogel loaded with exosomes (also expressed as: hydrogel-Exos or SIS gel-Exos)
[0224] According to the method of step 3 in Preparation Example 1, SIS pregel loaded with Exos was obtained, and placed at 37°C for 30 minutes to obtain SIS hydrogel loaded with exosomes.
[0225] In the specification, the composite hydrogel coaxial stent is also referred to as a double-layer composite stent.
[0226] Test Case
[0227] Test Example 1
[0228] 1. The morphology of Exos obtained in step 2 of Preparation Example 1 was observed by transmission electron microscopy (TEM, Hitachi, HT7700, Japan). The particle size and distribution of Exos were observed by nanoparticle tracking analysis (NAT, Nanosight NS300, UK). The markers of Exos were identified by western blot, with cytochrome C as a negative control.
[0229] Experimental results: BMSCs-derived Exos were extracted from the culture medium of BMSCs by ultracentrifugation. Figure 1A The successful extraction of Exos was confirmed by transmission electron microscopy (TEM), nanoparticle size analysis (NTA) and Western blot. Figure 1B-Figure 1E ).
[0230] 2. In order to detect the uptake of BMSCs-derived Exos by BMSCs and HUVECs, the Exos obtained by centrifugation were labeled with DiI (Beyotime, China), and the labeled Exos were incubated with BMSCs and HUVECs for 24 hours and 48 hours, respectively. Then they were washed with PBS, fixed in 4% paraformaldehyde (Solarbio, China) for 30 minutes, permeated with 0.5% Triton X-100 (Solarbio, China) for 10 minutes, and washed again with PBS. The nuclei were stained with DAPI solution (Solarbio, Beijing, China). Images were taken using a confocal laser scanning microscope (CLSM, LSM800, Zeiss, Germany).
[0231] The prepared Exos-loaded SIS pregel was placed at 37°C for 30 minutes to obtain an exosome-loaded SIS hydrogel (Preparation Example 8). In order to identify whether the SIS hydrogel loaded with exosomes is loaded with Exos, CLSM was used to observe the DiI-labeled Exos in the hydrogel, and the SIS hydrogel scaffold without Exos (Preparation Example 6) was used as a negative control.
[0232] Experimental results: Through CLSM images, it can be observed that the exosomes labeled with DiI in the SIS hydrogel loaded with exosomes (hydrogel-Exos) show red fluorescence ( Figure 1F ), proving that Exos were successfully loaded into the exosome-loaded SIS hydrogel.
[0233] In order to explore the stability of exosomes in the coaxial scaffold, the double-layer composite scaffold (Preparation Example 4) and the exosome-loaded SIS hydrogel (Preparation Example 8) were placed in PBS and incubated at 37°C for 14 days, and the cumulative release of exosomes was calculated using a BCA protein detection kit (Solarbio, China).
[0234] Experimental results: Figure 1G is the release curve of exosomes. Compared with the SIS hydrogel loaded with exosomes (SIS gel-Exos), the cumulative release curve of the SIS / HA+gel-Exos double-layer composite scaffold shows a continuous and slow release of exosomes, which is because the release of exosomes needs to pass through the SIS gel and SIS / HA double-layer structure. Starting from the 10th day, the release of exosomes in SIS gel reached equilibrium, while the SIS / HA+gel-Exos double-layer composite scaffold released a cumulative amount of about 57.32% on the 10th day. Therefore, the SIS / HA+gel-Exos double-layer composite scaffold has a better effect on the loading and sustained release of exosomes. Figure 1H and Fig. 1IThese are laser confocal images of Exos expression in HUVECs and BMSCs. The CLSM images show that Exos (red, DiI labeled) are taken up by cells and distributed around the nucleus (blue, DAPI), and the number of Exos taken up by cells incubated for 48 hours is greater than that of cells incubated for 24 hours, indicating that Exos can be taken up into the cytoplasm by BMSCs and HUVECs.
[0235] In addition, by measuring the difference in absorbance between the stent soaked in the antimicrobial peptide solution for 30 minutes and the 1 mg / ml antimicrobial peptide solution without soaking, it was calculated that about 4.907 μg of antimicrobial peptide was loaded per 1 mg of carrier stent. The antimicrobial peptide binding rate on the carrier stent was calculated to be about 80%.
[0236] The antimicrobial peptide binding rate refers to the degree of mutual binding between the stent surface and the drug molecules through physical or chemical interaction, usually expressed as a percentage. It reflects the stent material's ability to adsorb or fix drugs: binding rate (%) = (amount of drug after binding / initial drug amount) × 100%.
[0237] Test Example 2
[0238] 1. In order to characterize the SIS / HA+gel double-layer composite scaffold, the SIS / HA scaffold (SIS / HA; Preparation Example 5) and the SIS hydrogel scaffold (SIS gel; Preparation Example 6) were set as controls. The morphologies of SIS / HA, SIS gel, SIS / HA-gel (Preparation Example 2), and GL13K-SIS / HA+gel-Exos composite hydrogel coaxial scaffold (Preparation Example 1) were observed using scanning electron microscopy (SEM, ZEISS, Germany) and MicroCT, respectively.
[0239] Experimental results:
[0240] The characterization results of different scaffolds were analyzed. The surface morphology of different scaffolds was observed by SEM at different magnifications. The image of the SIS / HA scaffold showed that the HA particles were evenly distributed in the SIS collagen, and the freeze-dried SIS gel showed an interconnected porous network structure. In the SIS / HA+gel image, it can be seen that the hollow SIS / HA scaffold and the SIS gel are interconnected at the intersection of SIS collagen, proving that the coaxial scaffold was successfully prepared. Subsequently, the GL13K-SIS / HA+gel-Exos composite hydrogel coaxial scaffold ( Figure 2C In the figure, a large number of aggregated particles can be observed on the GL13K-SIS / HA+gel-Exos composite hydrogel coaxial scaffold (represented as G-SIS / HA+gel-Exos), which is the antimicrobial peptide GL13K.
[0241] 2. Micro CT was used to further scan the SIS / HA, SIS gel, SIS / HA+gel and GL13K-SIS / HA+gel-Exos scaffolds ( Figure 2D ), and three-dimensional images of different stents were reconstructed from two angles: lateral and cross-sectional.
[0242] Experimental results:
[0243] In the SIS / HA scaffold, HA particles and collagen are tightly combined, and a multi-porous structure that is interconnected can be seen. SIS gel shows the intricate interweaving structure of collagen fibers inside it. It is worth noting that in the SIS / HA+gel and GL13K-SIS / HA+gel-Exos scaffolds, the hollow area inside the SIS / HA hollow scaffold clearly shows the uniform filling of SIS gel.
[0244] 3. In order to explore the mechanical strength of the stent, a mechanical testing machine (3367, Instron, USA) was used to perform compression tests on each stent at a verification rate of 10 mm minutes. -1 .
[0245] Experimental results: The SIS / HA+gel scaffold was subjected to pressure compression test, with the SIS / HA scaffold and SIS gel as controls. The stress-strain curves of different scaffolds are shown in Figure 2. Fig.2I As shown in the figure, the stress-strain curve of SIS gel tends to be a straight line, indicating that the mechanical strength of SISgel is very low and collapses when subjected to stress. The SIS / HA scaffold prepared by adding HA particles to SIS gel undergoes elastic deformation in the initial stage, and the stress-strain increases in direct proportion. When the strain exceeds 1 mm, the SIS / HA scaffold is gradually compacted. Although the stress increases, the strain hardly changes. Therefore, the addition of HA significantly enhances the mechanical strength of the scaffold. In contrast, the strain of the SIS / HA+gel scaffold increases proportionally with the increase of stress. When the strain exceeds 0.7 mm, the stress-strain curve becomes flat, and the coaxial scaffold undergoes plastic deformation until the strain exceeds 1.5 mm, and the scaffold is slowly compacted. The results show that the SIS / HA+gel scaffold exhibits significant advantages over the SIS / HA scaffold and SIS gel. The SIS / HA+gel scaffold not only has good mechanical strength but also has a certain deformation ability. Figure 2E The deformation of the scaffold can be clearly observed in the figure. The SIS / HA+gel scaffold shows obvious deformation under slight compression, while the SIS / HA scaffold is relatively rigid. This improvement in deformation ability is mainly attributed to the unique hollow structure of the SIS / HA+gel scaffold containing SIS gel, which shows excellent compressibility.
[0246] 4. Grind the stent into fine powder and collect the infrared spectrum at 500-4000 cm using Fourier transform infrared spectrometer (FTIR) (Nicolet iS50, ThermoFisher Scientific, USA). -1 The porosity of each scaffold was calculated according to the formula (n=3): Porosity (%) = (V0-V e ) / (V t -V e )×100%, where V0 is the initial ethanol volume, V t V is the total volume of the scaffold after it is immersed in ethanol for 2 minutes. e The volume of ethanol after removing the scaffold. Each scaffold was freeze-dried and weighed to determine the initial weight M0, and then immersed in simulated body fluid (SBF) (Shyuanye, China). Placed in a 37°C constant temperature oscillating box for 7, 14, 21, 28, 35, and 42 days. The sample was dried at each time point to determine the weight M1 after degradation. The scaffold degradation rate was calculated according to the following formula = (M0-M1) / M0×100%. In order to detect the release of peptides in the GL13K-SIS / HA+gel-Exos (FITC-GL13K) double-layer composite scaffold, the scaffold was placed in PBS and slowly shaken (37°C, 60rpm) under dark conditions. The scaffold was taken out at a specific time period and the sample was observed by CLSM.
[0247] Experimental results:
[0248] Fourier transform infrared spectroscopy (FTIR) was used to detect the relevant chemical components of SIS / HA scaffold, SIS gel, SIS / HA+gel scaffold and GL13K-SIS / HA+gel scaffold. Figure 2F It can be observed that all scaffolds have typical absorption bands of collagen, and the amide I band is at 1646 cm -1 C=0 stretching vibration, amide II band at 1551cm -1 NH deformation and amide III band at 1400 cm -1 In addition, the NH deformation at 566 cm in the SIS / HA scaffold, SIS / HA+gel scaffold and GL13K-SIS / HA+gel scaffold -1 (OP-O bending vibration peak), 603cm -1 (PO4 3- The bending vibration peak of the group) and 1032cm -1 (PO4 3-The stretching vibration peak of the HA group showed a characteristic peak related to HA, indicating that HA particles were successfully incorporated into the SIS hydrogel. The spectrum of the GL13K-SIS / HA+gel scaffold showed that at 1570 cm -1 The characteristic peak of GL13K (amide II) is shown in Figure 2, proving the presence of GL13K in the GL13K-SIS / HA+gel-Exos scaffold.
[0249] Figure 2J The results showed that the porosity of SIS gel was 85.09%, while the porosity of SIS / HA scaffold was 66.37%, which may be caused by the filling of HA particles. The porosity of SIS / HA+gel scaffold was 75.37%, which was between the above two scaffolds. Therefore, SIS / HA+gel scaffold has a suitable porosity and can be used as a bone tissue engineering material.
[0250] 5. To study the release of GL13K on the GL13K-SIS / HA+gel-Exos scaffold, the amount of peptide on the coaxial scaffold after 1, 3, 5, and 7 days was observed by CLSM ( Figure 2G , Figure 2K ). On the first day, a large amount of FTIC-labeled GL13K was observed on the scaffold. Compared with the first day, the fluorescence intensity on the third day decreased significantly, indicating that GL13K directly loaded on the scaffold can be released into the surrounding environment in a short period of time. GL13K can still be observed on the scaffold surface until the seventh day, indicating that the peptide on the scaffold can be maintained for a certain period of time and continuously released into the surrounding environment.
[0251] Different scaffolds were immersed in simulated body fluid for 6 weeks to evaluate the degradation rate of the scaffolds. The results showed that the degradation rate of SIS gel was the fastest, while the degradation rate of SIS / HA scaffold, SIS / HA+gel and G-SIS / HA+gel-Exos scaffolds was slower, and there were still undegraded HA particles until the sixth week ( Figure 2H ), this slow degradation can provide time and space for new bone formation and more effectively maintain the volume of the alveolar ridge.
[0252] Test Example 3
[0253] 1. CCK-8 kit (Solarbio, China) was used to detect cell proliferation. BMSCs and HUVECs (6×10 3Cells / well) were inoculated in a 96-well plate and cultured with extracts from the scaffolds (SIS / HA+gel (Preparation Example 2), G-SIS / HA+gel (Preparation Example 3), SIS / HA+gel-Exos (Preparation Example 4), G-SIS / HA+gel-Exos (Preparation Example 1)), and the group with complete culture medium was the blank control group. After 1, 3, 5, and 7 days of culture, the absorbance (OD) value at 450 nm was measured using a microplate reader (Multiskan FC, Thermo Fisher Scientific, USA). In addition, to evaluate the cytotoxicity of the scaffold, BMSCs and HUVECs were co-cultured with the sample extracts for 3 days. The cells were stained with an AO / EB kit (Sangon Biotech, China), and cell viability was observed and images were taken using a fluorescence microscope (Olympus, Tokyo, Japan). The Transwell assay was used to detect the migration ability of cells in different groups. BMSCs and HUVECs (1×10 4 Cells) were inoculated in the upper chamber, and the sample extract (2% FBS) was placed in the lower chamber. After 24 hours, the culture medium was discarded and fixed with 4% paraformaldehyde for 30 minutes. Subsequently, 0.1% crystal violet (Solarbio, China) was added for staining for 20 minutes, and the non-migrated cells were gently wiped with a cotton swab. Images were taken by optical microscopy and analyzed with ImageJ software. In order to observe the cytoskeleton of different groups, BMSCs and HUVECs were inoculated in 24-well plates (1×10 4 After 24 hours of co-culture with sample extracts, cells / well) were fixed with 4% paraformaldehyde for 30 minutes and then permeabilized with 0.5% Triton X-100 for 10 minutes. Actin filaments were stained with rhodamine B-phalloidin (Cytoskeleton, Inc., USA), and cell nuclei were stained with DAPI (Solarbio, China). The cytoskeleton was observed by CLSM and images were taken.
[0254] Experimental results:
[0255] In order to clarify the effects of scaffold materials on cytotoxicity, proliferation and migration trends, the biocompatibility of different scaffolds (SIS / HA+gel (Preparation Example 2), G-SIS / HA+gel (Preparation Example 3), SIS / HA+gel-Exos (Preparation Example 4), G-SIS / HA+gel-Exos (Preparation Example 1), and blank control group) was deeply studied. Figure 3A Schematic diagram of cell behavior on G-SIS / HA+gel-Exos scaffolds. The proliferation activity of BMSCs and HUVECs was evaluated by C CK-8 assay. Figure 3BAs shown in Figure 2, a significant increase in cell number was observed during the extended culture period, especially in the G-SIS / HA+gel-Exos group, indicating a significant enhancement in cell proliferation. This proliferation may be due to the key role played by GL13K and Exos in the scaffold structure. In addition, the cytotoxicity of these scaffolds was evaluated using live / dead staining experiments. After 3 days of culture, BMSCs and HUVECs in all groups showed good growth with minimal dead cells ( Figure 3C ). These results collectively indicate that all scaffold groups exhibited satisfactory biocompatibility, which is essential for cell survival and subsequent tissue repair in vivo. Transwell assays were used to assess the migration capacity of B-MSCs and HUVECs ( Figure 3D ). After 24 h of culture, the number of migrating cells in the G-SIS / HA+gel, SIS / HA+gel-Exos, and G-SIS / HA+gel-Exos scaffolds was significantly higher than that in the blank group and SIS / HA+gel group. It is worth noting that the G-SIS / HA+gel-Exos group had the largest number of migrating cells. Quantitative analysis of the number of migrating cells ( Figure 3E-Figure 3F ) showed that there were significant differences between the G-SIS / HA+gel, SIS / HA+gel-Exos and G-SIS / HA+gel-Exos scaffolds and the blank and SIS / HA+gel groups, indicating that GL13K and Exos played a key role in promoting cell migration (P<0.05). After 3 days of culture on different scaffolds, the cell morphology and proliferation of BMSCs and HUVECs were evaluated by cytoskeleton staining. CLSM images showed that the number of B MSCs and HUVECs in the G-SIS / HA+gel-Exos group was significantly greater than that in the other groups. Compared with the blank and SIS / HA+gel groups, the BMSCs in the G-SIS / HA+gel, SIS / HA+gel-Exos and G-SIS / HA+gel-Exos scaffolds exhibited spindle-shaped stretched morphology, good ductility and extended cell pseudopodia. A dense actin filament network can also be observed ( Figure 3G For HUVECs, the cell expansion area observed in the blank group and SIS / HA+gel group was small and the cell morphology was not obvious. However, in the G-SIS / HA+gel, SIS / HA+gel-Exos, and G-SIS / HA+gel-Exos scaffolds, HUVECs showed polygonal morphology, obvious cell expansion, and orderly arranged red actin filaments were visible in the cells ( Figure 3H ). Therefore, the G-SIS / HA+gel-Exos coaxial scaffold significantly promoted the development of the cytoskeleton of BMSCs and HUVECs, providing an optimal growth environment for these cells.
[0256] 2. ECMatrix gel (Corning, 356234, USA) was used for in vitro angiogenesis experiments. After Matrigel was melted at 4°C, 60 μl was injected into a 96-well plate and placed at 37°C for 30 minutes to allow it to gel. Then, 3×10 4 HUVECs were seeded on the gel in the well plate, and the sample extract was added and cultured for 6 hours. The tube formation effect was observed by optical microscopy and analyzed by ImageJ software.
[0257] Inoculate 2×10 4 BMSCs were plated in 6-well plates. When the cells reached 70%-80% confluence, the medium was replaced with osteogenic induction medium (DMEM, 10% FBS, 1% penicillin and streptomycin, 50 μM ascorbic acid, 100 nM dexamethasone and 10 mM β-glycerophosphate (Sigma, USA). After 7 and 14 days of culture, the cells were stained and observed using a BCIP / NBT alkaline phosphatase color development kit (BCIP / NBT alkaline phosphatase color development kit; Beyotime, China). For ARS staining, after 14 and 21 days of culture, each group was stained with alizarin red solution (pH 4.2, Solarbio, China) for 20 minutes, gently rinsed with ddH2O, and observed and photographed using an optical microscope.
[0258] qPCR experiments were used to detect the expression of osteogenic and angiogenic related genes. HUVECs were cultured for 3 days, and BMSCs were cultured in osteogenic induction medium for 14 days. Total RNA was extracted using Trizol reagent (Invitrogen, USA). Then, cDNA was synthesized by reverse transcription using GoScript reverse transcription mix (Promega, USA). qPCR analysis was performed using SYBR Green Master Mix and Roche LC480II (Roche, Switzerland) system. The expression of related genes was normalized using GAPDH and 2 -ΔΔCt Methods Analysis of gene expression. Primer sequences were designed by Sangon Biotech, China.
[0259] First, protein extracts from HUVECs cultured for 3 days and BMSCs cultured for 14 days were extracted and diluted with protein loading buffer (5X, NCM Biotech, China). Each group of protein extracts was separated on 10% sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (Solarbio, China), and then transferred to polyvinylidene fluoride (PVDF) membranes (Sigma, USA) and electrophoresed at 300 mA for 100 minutes. The PVDF membrane was then blocked with 5% bovine serum albumin (BSA, Solarbio, China) for 1 hour and incubated with primary antibodies including anti-BMP2, anti-ALP, anti-OPN, anti-RUNX2, anti-VEGF, anti-HIF-1α and anti-GAPDH (1:1000 dilution, Abcam, Cambridge, UK) at 4 ° C overnight. Finally, the membrane was incubated with horseradish peroxidase (HRP)-conjugated secondary antibody (1:1000, Beyotime, China) at room temperature for 2 h, and the antibody-bound proteins were detected using an enhanced chemiluminescence (ECL) Western blotting analysis system (New Cell & Molecular, China). Band analysis was performed using Image J software, and all values were normalized to GAPDH values.
[0260] The expression of osteogenic and angiogenic related proteins was observed by cell immunofluorescence staining. BMSCs and HUVECs were inoculated in 24-well plates and cultured with sample extracts. The cells were fixed with 4% paraformaldehyde (Solomen, China) for 30 minutes and permeabilized with 0.5% Triton X-100 for 20 minutes. Then they were rinsed with PBS and blocked with BSA (5 mg / ml) solution for 30 minutes. The cells and primary antibodies including ALP, BMP2, RUNX2, VEGF and HIF-1α were incubated at 4°C overnight. Afterwards, the cells were incubated with Cy3-conjugated anti-rabbit secondary antibodies (1:1000, Abcam, UK) in the dark for 1 hour, and the cell nuclei were stained with DAPI (Solarbio, China) solution, and images were taken using CLSM.
[0261] Experimental results:
[0262] The angiogenesis potential of each group of scaffolds was verified by microtubule formation experiment, Western blot, PCR experiment, and immunofluorescence staining. The results showed that ( Figure 4A), after 6 hours of culture, HUVECs in the control group (blank) formed almost no vascular-like structures, while a small number of tubules were observed in SIS / HA+gel, which may be related to the presence of multiple active factors in SIS, including vascular endothelial growth factor and fibroblast growth factor. A large number of vascular-like structures were observed in G-SIS / HA+gel, SIS / HA+gel-Exos and G-SIS / HA+gel-Exos scaffolds, especially in the G-SIS / HA+gel-Exos group, where more tubules with more complete tubular structures were formed. In addition. The angiogenic ability of the G-SIS / HA+gel-Exos scaffold was further evaluated at the protein level. Western blot results ( Figure 4B-Figure 4C ) showed that the expression of angiogenesis-related proteins (HIF-1α and VEGF) was gradually upregulated in G-SIS / HA+gel, SIS / HA+gel-Exos, and G-SIS / HA+gel-Exos scaffolds. It is worth noting that the expression level in the G-SIS / HA+gel-Exos group was significantly higher than that in the control group and SIS / HA+gel group (P<0.05). In addition, immunofluorescence analysis ( Figure 4D-4F ) showed that the fluorescence intensity of HIF-1α and VEGF in the G-SIS / HA+gel-Exos group was much higher than that in other groups, and the fluorescence intensity of G-SIS / HA+gel and SIS / HA+gel-Exos scaffolds was similar. At the gene level, PCR detection evaluated the expression level of angiogenesis-related genes. Figure 4G The results showed that the mRNA expression levels (HIF-1α and VEGF) in the G-SIS / HA+gel-Exos group were significantly higher than those in the other groups (P<0.05). The above results indicate that the composite hydrogel coaxial scaffold loaded with GL13K and Exos plays an important role in promoting angiogenesis.
[0263] The potential osteogenic capacity of the coaxial scaffolds was determined and evaluated by ALP staining, ARS staining, Western blot, qPCR and immunofluorescence experiments. Figure 5A On days 7 and 14, the G-SIS / HA+gel-Exos group had the darkest staining, followed by G-SIS / HA+gel and SIS / HA+gel-Exos, while the SIS / HA+gel group had a slightly darker color than the blank group, which may be due to the presence of HA in the SIS / HA scaffold. A similar trend to ALP staining was observed in the ARS results ( Figure 5B). On day 14, scattered calcium nodule deposition appeared in all groups, and the G-SIS / HA+gel-Exos group had the largest number of calcium nodules. On day 21, compared with day 14, the number of calcium nodules in all groups increased significantly, and large calcium nodules were mainly found in the G-SIS / HA+gel-Exos group. This increase may be due to the stimulating effect of GL13K and Exos on the osteogenic differentiation and mineral deposition of BMSCs. To further clarify the effects of different scaffolds on the expression of osteogenesis-related proteins, protein immunoblotting analysis showed ( Figure 5C-5D ), the expression levels of osteogenic-related proteins (BMP2, ALP, OPN, and RUNX2) in the G-SIS / HA+gel-Exos group were the highest (P<0.05). In contrast, the protein expression levels in the G-SIS / HA+gel group and the SIS / HA+gel-Exos group were almost the same, with no significant difference (P>0.05). The results of qRT-PCR also confirmed this trend ( Figure 5E ), indicating that the expression levels of osteogenesis-related mRNA (BMP2, ALP, OPN, and RUNX2) in the G-SIS / HA+gel-Exos group were significantly upregulated, exceeding those in the other four groups (P<0.05). In addition, immunofluorescence staining images verified the expression of osteogenesis-related proteins (BMP2, ALP, and RUNX2). Specifically, the strongest red fluorescence was observed in BMSCs in the G-SIS / HA+gel-Exos group (P<0.05), indicating that the protein expression level was high ( Figure 6 The above results indicate that the composite hydrogel coaxial scaffold can support the proliferation and osteogenic differentiation of BMSCs. Compared with the SIS / HA scaffold, the G-SIS / HA+gel-Exos scaffold enhanced the osteogenic differentiation of cells under the action of GL13K and Exos.
[0264] Test Example 4
[0265] Inhibition ring test: Prepare LB solid culture medium plates and CDC anaerobic blood agar plates. Take 100ul of diluted Sa (Staphylococcus aureus) and Ss (Streptococcus sanguinis) bacterial solution and spread it evenly on the LB solid culture medium plate, and spread Fn (Fusobacterium nucleatum) bacterial solution on the CDC anaerobic blood agar plate. Then place the sterilized bracket on the plate, incubate it in a 37℃ incubator for 24h, take it out, take pictures and measure the diameter of the inhibition ring.
[0266] Live / dead bacterial staining: The survival of bacteria was detected by using a Live / dead staining kit (Life Technologies Corporation, CA). 2 ml of bacterial solution was aspirated into a 24-well plate with a cell slide, and co-cultured with the scaffold at 37°C for 24 hours. The bacterial solution was discarded and the working solution was added for staining. Dead bacteria (red) and live bacteria (green) can be observed by CLSM. Plate colony count: After placing the scaffold in 2 ml of bacterial solution and co-cultured at 37°C for 24 hours, 1 ml of bacterial solution was aspirated and diluted 10 with liquid culture medium. 3 -10 5 Then, 100 μl of Sa and Ss bacterial solution was spread on LB solid medium plate, and 100 μl of Fn bacterial solution was spread on CDC anaerobic blood agar plate. After 24 hours, the bacterial colonies on the plate were observed, pictures were taken with a camera and counted using ImageJ software.
[0267] Bacterial morphology: The morphology of bacteria on the surface of the scaffold was examined by SEM. After 2 ml of bacterial solution was added to a 24-well plate and co-cultured with the scaffold at 37°C for 24 hours, it was gently washed with sterile PBS and fixed overnight in 2.5% glutaraldehyde (Leagene, China) at 4°C. After fixation, the scaffold was placed in 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% ethanol solutions for gradient dehydration for 10 minutes each time. After the scaffold was dried, it was sprayed with gold and observed using SEM.
[0268] Experimental results:
[0269] The oral cavity is a habitat for a variety of microorganisms, so it is necessary to prevent infections associated with stent implantation. During the implantation process, a variety of bacteria may attach to the biomaterials and eventually lead to infection. Among them, Staphylococcus aureus is a Gram-positive aerobic bacterium and a common pathogen associated with infection of implanted biomaterials. In addition, Fusobacterium nucleatum and Streptococcus sanguinis often appear in the oral cavity as Gram-negative anaerobe and Gram-positive facultative anaerobe, respectively. In order to study the antibacterial activity of coaxial stents, we used the above bacteria as representatives and evaluated them by scanning electron microscopy, plate colony counts, bacterial live / dead staining and inhibition zone experiments. In order to study the antibacterial activity of coaxial stents, we evaluated them by SEM, plate colony counts, bacterial live / dead staining and inhibition zone experiments. The stent containing GL13K has a significant antibacterial effect on relevant bacteria during implantation. As Fig. 7AAs shown, a large number of bacteria were attached to the surface of the blank group (no scaffold was used), SIS / HA+gel group (Preparation Example 2) and SIS / HA+gel-Exos group (Preparation Example 4), and the bacterial film was intact, while the number of bacteria on the surface of the G-SIS / HA+gel group (Preparation Example 3) and G-SIS / HA+gel-Exos group (Preparation Example 1) was significantly reduced, indicating that the bacteria were broken, deformed or wrinkled on the surface. Plate colony count results ( Figure 7B-Figure 7C ) showed that compared with the blank group, SIS / HA+gel group, and SIS / HA+gel-Exos group, the number of bacterial colonies in the G-SIS / HA+gel group and the G-SIS / HA+gel-Exos group was significantly reduced, and only a small number of bacterial colonies were observed (P<0.05). The antibacterial effect of the coaxial stent loaded with GL13K was further evaluated by live / dead bacterial staining. Fig.7D The results showed that the number of live bacteria in the blank group, SIS / HA+gel group and SIS / HA+gel-Exos group was significantly higher, while the proportion of dead bacteria in the G-SIS / HA+gel group and G-SIS / HA+gel-Exos group was higher. Fig. 7E ) showed that no inhibition zone was observed around the stents in the blank group, SIS / HA+gel group, and SIS / HA+gel-Exos group, while obvious inhibition zones were observed around the stents in the G-SIS / HA+gel group and G-SIS / HA+gel-Exos group in three different bacterial plates. Statistical analysis showed that there was no significant difference in the diameter of the inhibition zone between the G-SIS / HA+gel group and the G-SIS / HA+gel-Exos group, but there was a significant difference compared with the other three groups (P<0.05).
[0270] The above experimental results show that the stent containing GL13K has a significant antibacterial effect on related bacteria during implantation. In the early stage of stent implantation, the G-SIS / HA+Gel-Exos coaxial stent can quickly release GL13K from the stent in large quantities, so that the GL13K around the stent reaches a local high concentration level in the early stage, and is slowly released in the later stage, effectively killing Gram-positive and Gram-negative bacteria adhering to the surface and surrounding of the stent, providing a favorable platform for the later bone repair process. Studies have found that most antimicrobial peptides (AMPs) penetrate the bacterial membrane with negative charges, destroy its integrity, and cause bacterial lysis and death. Therefore, compared with the use of antibiotics, GL13K as a cationic antimicrobial peptide can avoid the risk of bacterial resistance and play an antibacterial role more safely and effectively.
[0271] Test Example 5
[0272] This experiment was approved by the Animal Ethics and Welfare Committee of Tianjin Medical University. A rat alveolar bone defect model was used to evaluate the bone regeneration potential of the double-layer composite scaffold. Male SD rats were used in this experiment and randomly divided into 5 groups: blank group (Blank), SIS / HA+gel (Preparation Example 2), G-SIS / HA+gel (Preparation Example 3), SIS / HA+gel-Exos (Preparation Example 4), and G-SIS / HA+gel-Exos (Preparation Example 1). After the rats were anesthetized by inhalation of isoflurane, the gingiva was first gently separated with a dental probe, and then the crown was clamped with a vascular clamp. The first maxillary molar on the right side was extracted, rinsed with saline, and a 2mm diameter drill was used to form an alveolar bone defect with a diameter of 2mm and a depth of 2mm at the extraction site. Then the scaffold was placed in the extraction socket, and the alveolar socket without the scaffold was used as a blank control. Finally, the mucosal tissue around the wound was sealed with cyanoacrylate adhesive. Three days after the scaffold was implanted, the rats were killed, and the implantation site was checked for bacterial infection by plate colony count. Micro-CT: Rats were killed one month after surgery, and the maxilla was obtained and fixed in 4% tissue cell fixative (Solarbio, China). The maxilla was reconstructed by scanning with Micro-CT (SkyScan1276, Germany). The images of the maxilla 3D reconstruction were viewed by CTvox software, and the new bone volume fraction (BV / TV), bone mineral density (BMD) and trabecular thickness of the defect site were analyzed by CTAn software. The new bone formation in the defect area was viewed in the sagittal direction by Dataview software. Histological and immunochemical staining: The maxillary specimens were decalcified with EDTA decalcification solution (pH7.2, Solarbio, China) for 1 month, then dehydrated, embedded and cut into thick sections. Hematoxylin and eosin (HE) and Masson's trichrome staining were used. For immunohistochemical staining, the sections were incubated with primary antibodies including anti-OCN and anti-CD34 antibodies at 4°C overnight, and then treated with secondary antibodies.
[0273] Experimental results:
[0274] To evaluate the bone regeneration effect of the scaffold in the alveolar bone defect, the maxillary right first molar was extracted and a rat alveolar bone defect model was established ( Fig. 8A ). Three days after implantation, the colony counts were performed on the wound site. The results showed that the release of GL13K maintained good local antibacterial properties during bone repair ( Figure 8B ). Observe the sagittal image of the extraction socket through Dataview ( Figure 8C ), the blank group showed obvious horizontal absorption of alveolar bone to the root apex of the second molar, which was concave. In the experimental group, different degrees of alveolar bone regeneration were observed in the extraction socket, and the extraction socket of the G-SIS / HA+gel-Exos group was almost completely healed. Micro-CT reconstructed image ( Fig.8D ) showed that most of the defect areas in the blank group had not healed, and only a very small amount of regenerated bone was visible at the bottom of the extraction socket. Compared with the defect model established in the experimental group, the defect area was significantly reduced after the implantation of the scaffold, and bone regeneration was induced to varying degrees. In order to illustrate the regenerative effect of the coaxial scaffold in bone defects, we constructed a three-dimensional model of the new bone tissue ( Fig. 8E ). The amount of bone repair in the alveolar socket of the blank group was less than that of the other groups, and the bone regeneration effect of the G-SIS / HA+gel-Exos group was the most significant. In the horizontal sections, as the reconstruction process progressed, new bone was seen to form around the SIS / HA, G-SIS / HA+gel, and SIS / HA+gel-Exos scaffolds. At the same time point, the G-SIS / HA+gel-Exos group had more new bone formation in the center of the defect. In the G-SIS / HA+gel-exos group, the amount of new alveolar bone generated extending from the edge of the defect to the center was the largest, that is, the BMSCs-Exos in the SIS gel in the coaxial scaffold promoted cell proliferation and migration into the scaffold, and played an important role in osteogenesis. According to the quantitative analysis of Micro-CT, the bone volume / total volume (BV / TV), bone mineral density (BMD), and trabecular thickness of the different groups were compared, and the results showed that ( Figure 8F ), the bone volume / total bone volume and bone density of the scaffold implanted group were higher than those of the blank group, among which the bone volume / total bone volume (BV / TV) and bone density (BMD) of the G-SIS / HA+gel-Exos group were the highest. The trabecular thickness of the SIS / HA+gel-Exos group, the G-SIS / HA+gel group, and the G-SIS / HA+gel-Exos group were higher than those of the SIS / HA+gel group and the blank group, and there were significant statistical differences (P<0.05). New bone formation was further analyzed by H&E and Masson's trichrome staining. Figure 8G As shown, after 1 month, the blank group and SIS / HA+gel group had less bone tissue formation at the defect site, which was mainly filled with fibrous connective tissue, while the G-SIS / HA+gel-Exos group had better new bone formation and mineralization, and abundant blood vessels were visible. Immunohistochemical staining was used to evaluate the expression of osteogenic and angiogenic genes, among which OCN and CD34 are specific osteogenic markers and markers of endothelial progenitor cell formation during neovascularization, respectively. Figure 8H As shown in the figure, compared with the blank group and SIS / HA+gel group, the expression of OCN and CD34 in the G-SIS / HA+gel group and SIS / HA+gel-Exos group was significantly enhanced, and it was more obvious in the G-SIS / HA+gel-Exos group, indicating that the G-SIS / HA+gel-Exos scaffold effectively promoted osteogenesis and vascularization in the extraction socket.
[0275] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0276] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A composite hydrogel coaxial stent, characterized in that: include: A carrier scaffold, the carrier scaffold comprising a scaffold body having a cavity formed by a gel mixture, and the gel mixture contains a first hydrogel component and an osteogenic induction component; as well as The inner core is filled in the cavity of the carrier support, and the inner core comprises a second hydrogel component.
2. The composite hydrogel coaxial stent according to claim 1, characterized in that: In the carrier scaffold, the mass ratio of the first hydrogel component to the osteogenic induction component is 1:(5-15).
3. The composite hydrogel coaxial stent according to claim 1 or 2, characterized in that: The carrier scaffold is loaded with antimicrobial peptides; Preferably, the antimicrobial peptide comprises a cationic antimicrobial peptide; More preferably, the antimicrobial peptide comprises the amino acid sequence shown in SEQ ID NO: 1, or an amino acid sequence having one, two, three, four or five conservative substitutions compared with the amino acid sequence shown in SEQ ID NO:
1.
4. The composite hydrogel coaxial stent according to any one of claims 1 to 3, characterized in that: Every 1 mg of the carrier scaffold is loaded with more than 1 μg of the antimicrobial peptide, preferably more than 2 μg of the antimicrobial peptide.
5. The composite hydrogel coaxial stent according to any one of claims 1 to 4, characterized in that: The second hydrogel component is loaded with exosomes.
6. The composite hydrogel coaxial stent according to claim 5, characterized in that: The exosomes are derived from mesenchymal stem cells; Preferably, the exosomes are derived from bone marrow mesenchymal stem cells.
7. The composite hydrogel coaxial stent according to any one of claims 1 to 6, characterized in that: The first hydrogel component and the second hydrogel component each independently include one or a combination of two or more of porcine small intestinal submucosal gel, alginate, hyaluronic acid or collagen; Preferably, the first hydrogel component and the second hydrogel component each independently comprise porcine small intestinal submucosal gel; and / or, The osteoinductive component includes one or a combination of two or more of hydroxyapatite, tricalcium phosphate, tetracalcium phosphate, octacalcium phosphate, calcium oxide, calcium silicate, calcium sulfate or calcium carbonate; Preferably, the osteoinductive component comprises hydroxyapatite.
8. A method for preparing the composite hydrogel coaxial stent according to any one of claims 1 to 7, characterized in that: The following steps are involved: The step of preparing a carrier scaffold, wherein the osteogenic induction component is mixed with the first hydrogel component, added into a mold, and dried to obtain a carrier scaffold having a cavity; as well as The step of filling the inner core is to fill the second hydrogel component into the cavity of the carrier stent to form a composite hydrogel coaxial stent.
9. The preparation method according to claim 8, characterized in that: In the step of filling the inner core, the second hydrogel component is loaded with exosomes; Optionally, before the step of filling the inner core, a step of gel-loading exosomes is included, which includes mixing the second hydrogel component with a solution containing exosomes to obtain a second hydrogel component loaded with exosomes.
10. The preparation method according to claim 8 or 9, characterized in that: After the step of preparing the carrier support, the method further comprises the step of loading the carrier support with an antimicrobial peptide, wherein the carrier support is immersed in a solution containing the antimicrobial peptide to obtain the carrier support loaded with the antimicrobial peptide; Preferably, in the solution containing the antimicrobial peptide, the concentration of the antimicrobial peptide is 0.1-10 mg / mL.
11. Any of the following uses of the composite hydrogel coaxial scaffold prepared by the composite hydrogel coaxial scaffold according to any one of claims 1 to 8 or the preparation method according to any one of claims 9 to 10: (i) Use in the preparation of biological transplant materials; (ii) Use in the preparation of products for bone repair; (iii) Use in the preparation of bone regeneration products.
12. The use according to claim 11, wherein The biological transplant material is a biological transplant material used in the alveolar socket after tooth extraction; or The bone repair product is a bone repair product used to fill the alveolar socket after tooth extraction; or The bone regeneration product is a bone regeneration product used for filling the alveolar socket after tooth extraction.